Inoperable or incompletely resected craniofacial osteosarcoma treated by particle radiotherapy - Seidensaal, Katharina; Dostal, Matthias; Liermann, Jakob; Adeberg, Sebastian; Weykamp, Fabian; Schmid, Maximillian P.; Freudlsperger, Christian; Hoffmann, Jürgen; Hompland, Ivar; Herfarth, Klaus; Debus, Jürgen; Harrabi, Semi B. (Frontiers in oncology, 2022)
To report survival of craniofacial osteosarcoma patients treated by particle radiotherapy.
Gesehen am 13.10.2022